DILEMA ALIANSI AMERIKA SERIKAT TERKAIT PENINGKATAN KAPABILITAS MILITER JEPANG - Meidy Amanda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2018)
This paper examine the enhancement of military alliance between Japan and Unites States under Japan constitution. After the World War 2, Japan’s loss left Japan without enough defense to protect its country. Under the San Francisco Agreement, the United States and Japan make a Security Cooperation. With all the dynamics on the International Relation, United States and Japan have enhance their security alliance. This research will use alliance dilemma theory by Glenn H. Snyder. According to Snyder when the alliance is formed, the state has two choices in its alliance, cooperate or defect. The risk is when a state decided to make an alliance, the state will entrapped on the alliance. While if a state decided to defect, the state will get abandonment. So, this paper will examine the decision of the United States. In this case, enhancement of the security cooperation between United States and Japan is caused by alliance dilemma that make United States does not want to be entrapped into a regional conflict over an ally which is Japan.